2013
DOI: 10.5012/bkcs.2013.34.2.433
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrochemical Properties of Li3V2(PO4)3-LiMnPO4Composite Cathode Material for Lithium-ion Batteries

Abstract: Carbon-coated Li 3 V 2 (PO 4 ) 3 -LiMnPO 4 composite cathode materials are first reported in this work, prepared by the mechanochemical process with a complex metal oxide as the precursor and sucrose as the carbon source. X-ray diffraction pattern of the composite material indicates that both olivine LiMnPO 4 and monoclinic Li 3 V 2 (PO 4 ) 3 co-exist. We further investigated the electrochemical properties of our Li 3 V 2 (PO 4 ) 3 -LiMnPO 4 composite cathode materials using galvanostatic charging/discharging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…All the experimental results indicated that the electrochemical performances of the composites were improved. However, the rate performances of xLiMnPO 4 ·yLi 3 V 2 (PO 4 ) 3 composites (x≥y) are still poor in recent studies, as the diffusion of lithium ions were limited under high rate charge-discharge cycle process [8,11,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the experimental results indicated that the electrochemical performances of the composites were improved. However, the rate performances of xLiMnPO 4 ·yLi 3 V 2 (PO 4 ) 3 composites (x≥y) are still poor in recent studies, as the diffusion of lithium ions were limited under high rate charge-discharge cycle process [8,11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a series of xLiMnPO 4 ·yLi 3 V 2 (PO 4 ) 3 composites have been prepared by various approaches, including the chemical reduction and lithiation [8], spray-drying [9], solid-state reaction [10,11], solution [7] and so-gel [12] methods. All the experimental results indicated that the electrochemical performances of the composites were improved.…”
Section: Introductionmentioning
confidence: 99%
“…To briefly summarize, cationic or anionic doping of LVP induces defects in the host lattice and strength the crystal framework by enhancing the electrical and ionic conductivity and stabilizing the crystal structure in the charge/ discharge process of LVP. In particular, foreign atoms with a larger radius can expand the cell volume to facilitate Li-ion migration, which notably enhances the electrochemical performances of the LVP host, especially at high current rates ( [190][191][192][193] and LiCoO 2 [194]. (3) LVP with metals, for example, Ag [195,196] and Cu [197].…”
Section: Enhancing the Specific Capacity And Optimizing The Dischargimentioning
confidence: 99%
“…Their results showed that the hybrid cathode with a 1 : 1 mass ratio gave better performances than the other mass ratios. Sadeghiet al [38] and Yun et al [40] have also prepared these hybrid cathodes in a slightly different manner where they used one cathode as the parent (main material) and the other as the coating or modifying material. Therefore, the parent is in higher ratio than the coating material.…”
Section: Introductionmentioning
confidence: 99%